2022
DOI: 10.1111/aji.13612
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell profiles in recurrent pregnancy loss: Increased expression and positive associations with TACTILE and LILRB1

Abstract: Problem: NK cells are important for healthy pregnancy and aberrant phenotypes or effector functions have been associated with RPL. We compared expression of a broad panel of NK cell receptors, including immune checkpoint receptors, and investigated their clinical association with RPL as this might improve patient stratification and prediction of RPL. Method of study:Peripheral blood mononuclear cells were isolated from 52 women with RPL and from 2 women with an uncomplicated pregnancy for flowcytometric analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…It has been suggested that these cells could account for the greater likelihood of success in second and subsequent pregnancies (49) and if so, this would be consistent with a role for LILRB1 in optimizing placental development. For women with reproductive failure, studies on LILRB1 have mostly concentrated on pNK in RM patients (39,50) except for one study on uNK using termination samples stratified by uterine artery resistance (51). On balance, and in line with our findings, these studies reported reduced expression of LILRB1 in women with high risk of reproductive problems.…”
Section: Discussionsupporting
confidence: 81%
“…It has been suggested that these cells could account for the greater likelihood of success in second and subsequent pregnancies (49) and if so, this would be consistent with a role for LILRB1 in optimizing placental development. For women with reproductive failure, studies on LILRB1 have mostly concentrated on pNK in RM patients (39,50) except for one study on uNK using termination samples stratified by uterine artery resistance (51). On balance, and in line with our findings, these studies reported reduced expression of LILRB1 in women with high risk of reproductive problems.…”
Section: Discussionsupporting
confidence: 81%
“…Notably, a recent study by Habets et al found increased expression of CD96 on PBMCs from recurrent pregnancy loss samples, in contrast to the current study that found reduced CD96 expression on dNK cells. Many phenotypic differences between peripheral blood immune cells and maternal–foetal interface immune cells have been reported, and the underlying mechanisms of the differential phenotypic changes in CD96 at the peripheral blood and maternal–foetal interfaces need further exploration [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that these cells could account for the greater likelihood of success in second and subsequent pregnancies (Goldman-Wohl et al ., 2019) and if so, this would be consistent with a role for LILRB1 in optimizing placental development. For women with reproductive failure, studies on LILRB1 have mostly concentrated on pNK in RM patients (Kniotek et al ., 2021; Habets et al ., 2022) except for one study on uNK using TOP samples stratified by uterine artery resistance (Wallace et al ., 2014). On balance, and in line with our findings, these studies reported reduced expression of LILRB1 in women with high risk of reproductive problems.…”
Section: Discussionmentioning
confidence: 99%